Training on Creating Simple Renewable Energy Projects Based on STEM -SDGs (Sustainable Development Goals) to Introduce SDG-Based Education - Muttaqin, Muttaqin; Efwinda, Shelly; Hakim, Abdul; Syam, Muliati; Palian, Yolanda Oktavia (Universitas Lambung Mangkurat, 2025)
Energy is an important component in human life that is currently feared to be experiencing a shortage. This is because the main energy source used is fossil energy sources, which are limited and not environmentally friendly. This Community Service aims to introduce SDG-based education on the SDG's topic of using renewable energy sources to foster students' understanding and awareness of sustainable energy practices. This Community Service activity uses an Asset-Based Community Development (ABCD) approach, which focuses on identifying and utilizing the strengths and resources of the community and region, especially Samarinda, to support the integration of renewable energy education. This community service was carried out at State High School 4 Samarinda. The participants were all students from one of the classes who had or were taking subjects on renewable energy sources. The number of students who took part in this activity was 30 students. Data was obtained through project testing and questionnaires, which were distributed after the activities had been completed. The questionnaire consists of 10 questions, 8 of which are open questions. All groups succeeded in creating projects, and 86% of students responded positively to the SDGs. These results indicate that this educational activity has achieved its objectives regarding student understanding and awareness.